The Relationship Between Family Experiences and Motivation to Learn Science for Different Groups of Grade 9 Students in South Africa. Issue 1 (2nd January 2016) - Schulze, Salomé; Lemmer, Eleanor
Abstract : Worldwide science education is a national priority due to the role played by science performance in economic growth and the supply and quality of the human capital pool in scientific fields. One factor that may impact on the motivation to learn science is family experiences. This study therefore explored the relationship between family experiences and the motivation for science learning among a group of secondary school students in South Africa. A convenience and purposeful sample ( N = 380) were used. Criteria for inclusion stipulated that the students were Grade 9 boys and girls from different racial groups in public and private schools. Data on family experiences and motivation for science learning were collected using a structured questionnaire. Hypotheses were tested based on the correlations between the motivation for science learning and family experiences for gender, race, school and school type. Significant correlations were identified between family experiences (the distal and proximal dimensions) and the motivation for science learning for the sample. However, no significant differences were found between different student groups with regard to the above-mentioned correlations.